Mirabel’s Voice: A Critical Discourse and Socio-Cultural Analysis of Identity in Encanto Movie - Amalia, Tiara Surya; Amalia, Nabilla; Azizah, Helmanisa Nur (J-LELC: Journal of Language Education, Linguistics, and Culture, 2025)
This study investigates the construction of identity and voice through language, power, and culture in Disney’s Encanto (2021), with a particular emphasis on the character Mirabel Madrigal. Employing the Critical Discourse Analysis (CDA) methodology established by Fairclough (2013), the research examines how family communication patterns influence self-confidence and identity formation within a collectivist context. A qualitative descriptive methodology was implemented using primary data from chosen dialogues, lyrics, and visual moments in the film, alongside secondary data from academic journals and audience feedback collected via the Loklok platform.  The results indicate that linguistic components such as modality, labeling, and metaphor, serve as instruments of authority and emotional regulation. Abuela's authoritative speech and the family's quiet demonstrate discursive authority that stifles individuality, whereas Mirabel's defiance represents the reestablishment of voice and empowerment. The movie's visual metaphors, especially the falling Casita, show how people hide their feelings and how ideological control breaks away. Audience interpretations further emphasize the relevance of topics such as perfectionism, gender expectations, and generational trauma in authentic collectivist civilizations, including Indonesia. In conclusion, Encanto shows that healing and forming an identity both need open communication and empathy. It also shows how language and culture impact both individual and group change.